Implications of Digital Library Transformation on the Learning Process of Accounting Education Students - Dongoran, Faisal Rahman; Khairani, Suci; Fadhillah, Lola (Universitas Muhammadiyah Sumatera Utara (UMSU), 2024)
The purpose of this study was to determine the impact of digital Digital transformation in the library on the learning process of accounting education students, Faculty of Teacher Training and Education, Universitas Muhammadiyah Sumatera Utara, Indonesia. This research uses a quantitative approach because the observed phenomena are converted into numbers that are analysed using statistics. The sample in this study consisted of 79 students of accounting education programme. The results showed that there was an effect of digital transformation in the library on the students' learning process. This can be shown by the Fcount score of 97.639 with a significance level of 0.000 0.05, in other words, there is an influence of the library digital transformation variable (X) on the students' learning process (Y). In addition, the coefficient of determination (R2) of 0.559 or 55.9% is influenced by the digital transformation in the library and is significant for the learning process of the students of the accounting education programme, while the remaining 44.1% is influenced by other variables not studied.Keywords: Digital Transformation, Digital Library, Students’ Learning Process.